2014
DOI: 10.1021/ie503576d
|View full text |Cite
|
Sign up to set email alerts
|

The First Example of ortho-Arylation of Benzamides over Pd/Mesoporous Silica: A Novel Approach for Direct sp2 C–H Bond Activation

Abstract: Three-dimensional mesoporous silica with a highly dispersed palladium nanoparticles composite (PS-3) catalyst has been prepared and characterized by X-ray diffraction, X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, nitrogen sorption, and high resolution transmission electron microscopy. The PS-3 catalyst utilized for the first time as an efficient and reusable catalyst in the ortho-arylation of benzamides by aryl iodides has been demonstrated with the simplest amide CONH2 as a direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…In 2014, Srinivasu et al reported the first orthoarylation of benzamides 3 using a supported Pd catalyst: threedimensional mesoporous silica with highly dispersed palladium nanoparticles composite (named PS-3). 18 Direct C-H arylations were successfully performed between functionalized benzamides and aryl iodides with different stereo-electronic properties, in acetic acid as the solvent and silver acetate as the base, affording the ortho-arylated products 4 in reasonable yields, 36-76% (Scheme 3). Recyclability of PS-3 catalyst was also tested over five different cycles without significant loss of its activity.…”
Section: Recoverable Palladium-based Catalysts For Direct C-h Bond Ar...mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, Srinivasu et al reported the first orthoarylation of benzamides 3 using a supported Pd catalyst: threedimensional mesoporous silica with highly dispersed palladium nanoparticles composite (named PS-3). 18 Direct C-H arylations were successfully performed between functionalized benzamides and aryl iodides with different stereo-electronic properties, in acetic acid as the solvent and silver acetate as the base, affording the ortho-arylated products 4 in reasonable yields, 36-76% (Scheme 3). Recyclability of PS-3 catalyst was also tested over five different cycles without significant loss of its activity.…”
Section: Recoverable Palladium-based Catalysts For Direct C-h Bond Ar...mentioning
confidence: 99%
“…The protocol looks highly attractive from a Scheme 3 Direct C-H ortho-arylation of benzamides 3 with aryl iodides catalysed by Pd nanoparticles supported on three-dimensional mesoporous silica (PS-3), developed by Srinivasu et al in 2014. 18 Scheme 2 Direct C-H bond arylation of naphthalene 1 with aryliodonium salts catalysed by recoverable Pd/C catalyst, developed by Glorius and co-workers in 2015. 17 Green Chemistry point of view, since the supported palladium catalyst was used in combination with γ-valerolactone (GVL) as a sustainable and environmentally benign reaction medium (see section 3.3.4).…”
Section: Recoverable Palladium-based Catalysts For Direct C-h Bond Ar...mentioning
confidence: 99%
“…106 The PS-3 catalyst contains particles of approximately 7-8 nm which display well resolved (111), (200) and (220) planes, indicating face-centered cubic structures. 106 The PS-3 catalyst contains particles of approximately 7-8 nm which display well resolved (111), (200) and (220) planes, indicating face-centered cubic structures.…”
Section: Silicon-based Frameworkmentioning
confidence: 99%
“…Srinivasu and coworkers prepared a mesoporous silica with a highly dispersed palladium nanoparticle composite catalyst (PS-3) and tested it for the direct C-H arylation of benzamides 20 with aryl iodides 8 (Scheme 13). 29 The reaction occurred with excellent site-selectivity towards ortho-functionalization and was tolerant to the presence of functional groups, such as halides, ketones and ethers. Both electron-rich and electronpoor benzamides were competent substrates for the process.…”
Section: C-h Arylationmentioning
confidence: 99%